The Body as a Vessel for Trauma: The Clinical Case Study of Aisha - Federica Visco-Comandini; Alberto Barbieri; Francesco Mancini; Alessandra Ciolfi (Brain Sciences)
This case study examined the process of integration of cognitive behavioral therapy (CBT) and sensorimotor psychotherapy (SP) in three-phase trauma treatment with a 32-year-old female Bengali refugee with Complex Post Traumatic Disorder (C-PTSD). The treatment was provided in a Western country. The client’s improvement was assessed by using self-report assessments of post-traumatic, dissociative, and depressive symptoms. Psychodiagnostics’ scores gathered after 2 years of treatment showed significant improvements in post-traumatic, dissociative, and depressive symptoms. Although firm conclusions cannot be drawn due to the limitations of this study, results suggest that integrating CBT and SP in a phase-trauma approach may be an effective treatment for C-PTSD in a transcultural setting. However, replicating and standardizing such preliminary results on larger samples is necessary. Background/Objectives: SP is an innovative psychotherapeutic intervention aimed at treating trauma through a bottom-up approach, however, little research exists regarding the efficacy of this psychotherapy. This case study aims to investigate the efficacy of the combination of CBT and SP in treating a C-PTSD patient in a transcultural setting. Methods: Three questionnaires were administered to investigate post-traumatic, depressive, and dissociative symptoms. Results: Clinical and psychodiagnostic outcomes highlight significant psychological improvements in the patient. Conclusions: Although any firm conclusion cannot be drawn because of various intrinsic limitations (i.e., single case study) that straiten our ability to extend these results, this case study suggests that the integration of CBT and SP may be an effective treatment for C-PTSD in a transcultural setting.